The Power of Isti'ārah Metaphors in Contemporary Arabic Poetry al-Nahru al-‘Āshiq by Nāzik al-Malā’ikah - Devi Suci Windariyah (UIN Raden Mas Said Surakarta, 2026)
The metaphor of isti'ārah in contemporary Arabic poetry, such as in al-Nahru al-‘Āshiq written by Nāzik al-Malā’ikah, offers aesthetic depth and profound social critique. This research aims to analyze the power of isti'ārah as a means of expression in depicting social and emotional realities. Using an analytical descriptive qualitative method, this study explores the form and function of isti'arah in this poem. The main findings show the dominance of isti'ārah murosyahah, which constructs complexities of meaning and aesthetics that go beyond literal likeness. Metaphors also play an important role in bridging the individual and collective experiences of the reader. This research contributes to the enrichment of balāghah studies by bridging traditional Arabic approaches with modern metaphor theory, offering new insights for contemporary Arabic literary studies on a global level.